“Why won’t they mix?”: barriers to Indigenous/non-Indigenous youth relationships in Yukon high schools - Fabre-Dimsdale, Anyes (2020)
The Yukon territory is home to fourteen First Nations, eleven of them self-governing. Close to 25% percent of the Yukon’s population is Indigenous. In the 5 high schools of the Yukon’s capital city of Whitehorse however, interactions and relationships between the indigenous and non-indigenous students are often perceived as minimal and uneasy, as observed by parents, staff, and the students themselves, with social groups often divided between indigenous and non-indigenous youth. Using a non-traditional narrative approach focusing on the lived experiences of students, parents and staff, this paper seeks to examine and identify possible barriers to relationships between indigenous and non-indigenous youth in the schools, while collecting from project participants recommendations to better foster relationship building and connection between students, in support of a more welcoming, inclusive and culturally relevant high school community for Indigenous youth.